ANALISIS PENGARUH KOMUNIKASI, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT Smartfren Telecom Tbk di Sragen) - Bawono, Tri Agung; Budiwinarto, Kim (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
This study aims to determine the effect of comunication, work environment, and work motivation on employees performance at PT Smartfren Telecom Tbk in Sragen for the 2018-2021. This research is a quantitative assessment of the data collection method used in this study using a questionnaire by giving a set of questions or written questions to the respondent to answer. The analysis technique used is multiple linear regression model, t-test, F-test, and the coefficient of determination. The results of the analysis show that there is no effect of communication on employee performance. The influence of the work environment also has positive results and the influence of motivation on employees also has positive results in the company. When these variables have a positive effect and increase company productivity. These things indicate that the communication of work environment motivation is significant and improve employee performance and develop the idea of commitment and responsibility at work.